Identity and language learning gender, ethnicity and educational change - Norton, Bonny 1956- (Language in social life series, 2000)
Language in Social Life is a major series which highlights the importance of language to an understanding of issues of social and professional concern. It will be of practical relevance to all those wanting to understand how the ways we communicate both influence and are influenced by the structures and forces of contemporary social institutions. Under what conditions do language learners speak? How is a learner's changing identity related to the process of language learning? How can language teachers address the complex histories of language learners? These are the questions that are central to Identity and Language Learning: Gender, Ethnicity and Educational Change. Drawing on a longitudinal case study of immigrant women in Canada, Bonny Norton suggests that second language acquisition theory has not adequately formulated a conception of identity that integrates the language learner and the language learning context. Such theory, in particular, has not given sufficient attention to relations of power between language learners and target language speakers. She suggests that a poststructuralist conception of identity as multiple, a site of struggle, and subject to change is an important contribution to the field of language learning and teaching. Further, she argues for a conception of investment to capture the complex and sometimes ambivalent relationship of language learners to the target language. Integrating research, theory, and classroom practice, this book will be of interest to students, teachers, and researchers in the fields of second language learning and teaching, TESOL, applied linguistics and language planning.